Pemberdayaan Nelayan Melalui Rompong Berbasis Teknologi Untuk Meningkatkan Pendapatan Nelayan Di Desa Meli Kabupaten Donggala Provinsi Sulawesi Tengah - Jufri, Muhammad; Marwana, Marwana; Sulfiati, Sulfiati; Udin Sidik Sidin, Udin; Bakhrani A Rauf , Bakhrani; Rahmansah, Rahmansah (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2026)
Through the Kosabangsa Program, this community service activity aims to introduce and implement Rompong based on Solar Panel and Submersible Lamp (Lacuda) technology to coastal fishermen in Meli Village, Donggala Regency, Central Sulawesi Province. The main objective is to increase the income of coastal fishermen in Meli Village. The activity was attended by 20 participants and carried out through socialization, technical training, tool assembly practice, and direct trials. The results of the activity are technical guides for the use of Solar panels and Lacuda, which contain information on components, assembly, operation, and technical troubleshooting. Evaluation of the technical guide was carried out by calculating and comparing the catch of coastal fishermen in Meli Village before using Rompong based on Solar panel and Lacuda technology. This activity succeeded in transferring appropriate technology in a participatory and contextual manner, and opened up opportunities for further development in the coastal areas around Meli Village.